2016
DOI: 10.18203/2320-6012.ijrms20161199
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of feto-maternal outcome and complications in pregnancy induced hypertension from a tertiary level health care teaching institution of Tamil Nadu, India

Abstract: Background: Hypertensive disorder is the second most common medical disorder seen during pregnancy. They along with hemorrhage and infection, contribute greatly to maternal morbidity and mortality. Most deaths in PIH occur due to its complications and not due to hypertension per sec. Thus, maternal mortality and these complications are preventable. The objective of the present study was undertaken to study pattern of feto-maternal outcome and complications in cases of pregnancy induced hypertension with a view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Similarly in a study conducted by Jayaraman L LSCS was observed to be a more common mode of delivery. 7 In our study it was noted that higher percentage of outcome of PIH patients weighed between 2501-3000gms (41.2%) followed by 2000-2500gms (25.5%), more than 3000gms (19.6%) and less than 2000gms (13.7%). Twenty outcomes (40%) had weight less than 2500gm (low birth weight) out of which three had weight less than 1500gms (very low birth weight).…”
Section: Discussionmentioning
confidence: 44%
“…Similarly in a study conducted by Jayaraman L LSCS was observed to be a more common mode of delivery. 7 In our study it was noted that higher percentage of outcome of PIH patients weighed between 2501-3000gms (41.2%) followed by 2000-2500gms (25.5%), more than 3000gms (19.6%) and less than 2000gms (13.7%). Twenty outcomes (40%) had weight less than 2500gm (low birth weight) out of which three had weight less than 1500gms (very low birth weight).…”
Section: Discussionmentioning
confidence: 44%
“…Similarly in a study conducted by Jayaraman, LSCS was observed to be a more common mode of delivery. 13 Out of 51 PIH patients, there were 4 cases of gestational hypertension (7.85%), 38 cases of non-severe preeclampsia (74.50%), 8 cases of severe preeclampsia (15.69%) and 1 case of eclampsia (1.96%) in our study. In 4 cases of gestational hypertension, all 4 cases belong to mild variety.…”
Section: Discussionmentioning
confidence: 47%
“…Similarly in a study conducted by Jayaraman, LSCS was observed to be a more common mode of delivery. 10 According to our study, the most common complication was preterm delivery (43%) followed by IUGR (27%). The incidence of placenta abruption and eclampsia was found to be 6% and 15% respectively…”
Section: Discussionmentioning
confidence: 63%